STUDI ALTERNATIF PERENCANAAN STRUKTUR ATAS JEMBATAN PELENGKUNG PIPA BAJA DENGAN METODE DESAIN DENGAN METODE DESAIN FAKTOR BEBAN KETAHANAN (DFBK): Studi Kasus : Jembatan Pasopati Kota Madiun - NUKI TRI SUSANTO (STUDENT JOURNAL GELAGAR, 2022)
Arch Bridge is a bridge structure whose structural elements are curved along the span of the bridge. Arch-type bridges are good for bridges with medium spans because the short element length reduces the risk of buckling in the frame. Through this thesis the author tries to plan an alternative structural design for a steel arch bridge on the Bengawan river bridge in Madiun City. In this case the planning uses the DFBK (Load and Endurance Factor Design) method and for the modeling it uses the help of the SAP 2000 V19 program. Arch-type bridge superstructure consists of several main parts, namely longitudinal girders, transverse girders, main girders, upper wind ties, lower wind ties, stiffening girders, sidewalks, vehicle floors and elastomeric placement which form a rigid unit so that it is safe and comfortable in traffic on the bridge. As for the results of the planning and analysis obtained, the structure of the superstructure of the bridge uses a profile of WF 350 x 175 x 7 x 11 (longitudinal girder), WF 700 x 300 x 15 x 28 (transverse girder), WF 400 x 400 x 13 x 21 ( main girder), 0.6 m pipe (curved), 0.3 m pipe (wind ties).